2013
DOI: 10.1371/journal.pone.0066824
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Activation Mechanism of the Potato Tuber ADP-Glucose Pyrophosphorylase

Abstract: ADP-glucose pyrophosphorylase regulates the synthesis of glycogen in bacteria and of starch in plants. The enzyme from plants is mainly activated by 3-phosphoglycerate and is a heterotetramer comprising two small and two large subunits. Here, we found that two highly conserved residues are critical for triggering the activation of the potato tuber ADP-glucose pyrophosphorylase, as shown by site-directed mutagenesis. Mutations in the small subunit, which bears the catalytic function in this potato tuber form, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…As part of the identified heterogeneity among 20 monomers in one asymmetric unit, we were able to resolve, in some subunits, parts of the loop 96 -108. This loop has been implicated in regulation in both E. coli and potato tuber homologues (18,19). We identified that residues 96 and 97 (N-end of this loop) deviate nearly 180°from the direction previously reported.…”
Section: Newly Observed Structural Features Of the A Tumefaciens Adpmentioning
confidence: 56%
“…As part of the identified heterogeneity among 20 monomers in one asymmetric unit, we were able to resolve, in some subunits, parts of the loop 96 -108. This loop has been implicated in regulation in both E. coli and potato tuber homologues (18,19). We identified that residues 96 and 97 (N-end of this loop) deviate nearly 180°from the direction previously reported.…”
Section: Newly Observed Structural Features Of the A Tumefaciens Adpmentioning
confidence: 56%
“…S6 ). Catalysing the first committed step in starch biosynthesis, ADP-glucose pyrophosphorylase (AGPase) is a heterotetramer comprising a pair of small/catalytic and a pair of large/regulatory subunits ( Kim et al , 2007 ; Figueroa et al , 2013 ). Among the tomato genes encoding the large AGPase subunits, both SlAGPaseL1 and SlAGPaseL3 were up-regulated whereas SlAGPaseL2 mRNA levels remained unchanged in immature fruits of SlPHYA RNAi plants.…”
Section: Resultsmentioning
confidence: 99%
“…The LSUs mainly have regulatory roles and the SSUs have catalytic roles, and recent studies indicate that LSUs also contribute substrate binding (Cakir et al ., ; Hwang et al ., ; Kavakli et al ., ). AGPases are activated by 3‐phosphoglyceric acid and inhibited by inorganic phosphate (Boehlein et al ., ; Figueroa et al ., ; Heldt et al ., ; Neuhaus et al ., ). In nonphotosynthetic cells, AGPases have different localizations in dicots and monocots (Comparot‐Moss and Denyer, ).…”
Section: Introductionmentioning
confidence: 98%